RibScore: A novel radiographic score based on fracture pattern that predicts pneumonia, respiratory failure, and tracheostomy. Issue 1 (January 2016) - Chapman, Brandon C.; Herbert, Benoit; Rodil, Maria; Salotto, Jennifer; Stovall, Robert T.; Biffl, Walter; Johnson, Jeffrey; Burlew, Clay Cothren; Barnett, Carlton; Fox, Charles; Moore, Ernest E.; Jurkovich, Gregory J.; et al.
Abstract : BACKGROUND: There is currently no scoring system for rib fractures that relates detailed anatomic variables to patient outcomes. Our objective was to develop and validate a radiographic rib fracture scoring system based on computed tomographic chest findings. METHODS: We reviewed our trauma registry from September 2012 to April 2014 for all blunt trauma patients with one or more rib fractures visualized on chest computed tomography. We identified the following six candidate radiographic variables and tested their individual associations with pneumonia, respiratory failure, and tracheostomy: (1) six or more rib fractures, (2) bilateral fractures, (3) flail chest, (4) three or more severely (bicortical) displaced fractures, (5) first rib fracture, and (6) at least one fracture in all three anatomic areas (anterior, lateral, and posterior). We developed the "RibScore" by assigning 1 point for each variable, which was validated among the sample using univariate analyses, test performance characteristics, and the receiver operating characteristic area under the curve c statistic. RESULTS: A total of 385 patients with one or more rib fractures were identified; 274 (71.2%) were males, median age was 48 years, and median Injury Severity Score (ISS) was 17. Of these patients, 156 had six or more rib fractures, 120 had bilateral fractures, 46 had flail chest, 32 had three or more severely displaced fractures, 91 had a first rib fracture, and 58 had fractures in all three anatomic areas. Each RibScore component variable was associated with the three pulmonary outcomes by univariate analysis ( p < 0.05). The median RibScore was 1 (range, 0–6). The distribution of the RibScore was as follows: score of 0, 41.9%); score of 1, 23.9%; score of 2, 15.4%; score of 3, 9.9%; score of 4, 7.6%; and score of five, 1.3%. RibScore was linearly associated with pneumonia ( p < 0.01), acute respiratory failure ( p < 0.01), and tracheostomy ( p < 0.01). The receiver operating characteristic areas under the curve for the outcomes were 0.71, 0.71, and 0.75, respectively. CONCLUSION: The RibScore predicts adverse pulmonary outcomes and represents a standardized assessment of fracture severity that may be used for communication and prognostication of the severely injured trauma patient. LEVEL OF EVIDENCE: Prognostic study, level III. Abstract : Supplemental digital content is available in the text.